Calculation of high speed inlet flows using the Navier-Stokes equations. Volume 1, Description of results / Doyle D. Knight. - Knight, Doyle D.; Air Force Flight Dynamics Laboratory (U.S.); Rutgers University. Department of Mechanical & Aerospace Engineering (Wright-Patterson Air Force Base, Ohio : Air Force Flight Dynamics Laboratory, Air Force Systems Command, United States Air Force, 1980)
A set of computer programs has been developed to calculate the flowfield in two-dimensional mixed-compression high speed inlets. The full mean compressible Navier-Stokes equations are utilized, with turbulence represented by an algebraic eddy viscosity model which incorporates a relaxation correction. A curvilinear body-oriented coordinate system is employed to allow handling of arbitrary inlet contours. Boundary layer bleed is incorporated. The numerical algorithm of MacCormack is employed to solve the Navier-Stokes equations. A variety of techniques are incorporated to improve code efficiency, including time-splitting of the finite-difference operators, automatic mesh-splitting, and a separate algorithm for the treatment of the viscous sublayer portion of the turbulent boundary layers. The numerical codes have been successfully applied to the calculation of a variety of flows including shock-boundary layer interaction on a flat plate (including both unseparated and separated cases), and three different simulated high speed inlet configurations. In all cases, good agreement was obtained with the experimental data.
"February 1980."
Includes bibliographic references (pages 40-42)
Report supported by the Air Force Flight Dynamics Laboratory, Air Force Wright Aeronautical Laboratories, Air Force Systems Command, United States Air Force, and performed by Department of Mechanical, Industrial and Aerospace Engineering, Rutgers Univserity, New Brunswick, New Jersey, under contract no.
Mode of access: Internet.
Keywords: Turbulent boundary layer; Navier-Stokes equations; Airplanes -- Ramjet engines -- Air intakes